Recombinant live attenuated avian coronavirus vaccines with deletions in the accessory genes 3ab and/or 5ab protect against infectious bronchitis in chickens. Issue 8 (14th February 2018) - van Beurden, Steven J.; Berends, Alinda J.; Krämer-Kühl, Annika; Spekreijse, Dieuwertje; Chenard, Gilles; Philipp, Hans-Christian; Mundt, Egbert; Rottier, Peter J.M.; Verheije, M. Hélène
Highlights: Accessory genes 3 and 5 are not essential for IBV's replication in ovo and in vivo . IBVs lacking 3ab and/or 5ab reduce ciliostasis and are thus attenuated. The attenuated IBV strains can protect against homologues challenge. Targeted RNA recombination enables the development of live attenuated IBV vaccines. Abstract: Avian coronavirus infectious bronchitis virus (IBV) is a respiratory pathogen of chickens, causing severe economic losses in poultry industry worldwide. Live attenuated viruses are widely used in both the broiler and layer industry because of their efficacy and ability to be mass applied. Recently, we established a novel reverse genetics system based on targeted RNA recombination to manipulate the genome of IBV strain H52. Here we explore the possibilities to attenuate IBV in a rational way in order to generate safe and effective vaccines against virulent IBV (van Beurden et al., 2017). To this end, we deleted the nonessential group-specific accessory genes 3 and/or 5 in the IBV genome by targeted RNA recombination and selected the recombinant viruses in embryonated eggs. The resulting recombinant (r) rIBV-Δ3ab, rIBV-Δ5ab, and rIBV-Δ3ab5ab could be rescued and grew to the same virus titer as recombinant and wild type IBV strain H52. Thus, genes 3ab and 5ab are not essential for replication in ovo . When administered to one-day-old chickens, rIBV-Δ3ab, rIBV-Δ5ab, and rIBV-Δ3ab5ab showed reduced ciliostasis as compared to rIBV H52 and wild type H52, indicating that the accessory genes contribute to the pathogenicity of IBV. After homologous challenge with the virulent IBV strain M41, all vaccinated chickens were protected against disease based on reduced loss of ciliary movement in the trachea compared to the non-vaccinated but challenged controls. Taken together, deletion of accessory genes 3ab and/or 5ab in IBV resulted in mutant viruses with an attenuated phenotype and the ability to induce protection in chickens. Hence, targeted RNA recombination based on virulent IBV provides opportunities for the development of a next generation of rationally designed live attenuated IBV vaccines.